KLASIFIKASI KEPUASAN PELANGGAN COFFEE SHOP PATURUPA MENGGUNAKAN DECISION TREE - Siti Hinggit (2023)
Coffee shops are currently popular in Indonesia, and the current situation also allows coffee shops to compete to increase customer satisfaction. Paturupa one of coffee shop located in Bekasi want to know about how customer satisfaction in Paturupa and factor that is important for their customer satisfaction. For realizing, data are needed which are obtained from customer satisfaction questionnaires in Paturupa which are share through google forms. The data are obtained as many as 150 data with labels "Yes" and "No" which are divided into train data and test data. The train data are used to build a model with the Decision Tree C4.5 algorithm and use SMOTE and NearMiss for handling imbalanced data and obtained entropy and information gain values to determine the roots of nodes and other nodes. The best performance results are reached by this study with splitting data 70% for train data and 30% for test data that using NearMiss method, accuracy score is 96%, recall score is 100%, precision score is 95%, and specificity score is 75%.